Россия, Запад и эмиграция в сборнике Зиновия Зиника Эмиграция как литературный прием - Ludmiła Szewczenko (Polilog: Studia Neofilologiczne, 2022)
One of the predominant motives in Z.Zinyk’s collection of articles “Emigration as a Literary Technique” is the search by the author/narrator of their own self as seen by them from the inside, in the turned over perspective of the Soviet past, and from the outside, in a detached and estranged way, in the context of the emigrant’s reality.